PENGARUH LINGKUNGAN KERJA NON FISIK, ETOS KERJA DAN DISIPLIN KERJA TERHADAPPRODUKTIVITAS GURU DAN PEGAWAI DI SD SWASTA AL-AZHAR 1 MEDAN - Yocananda, Nabilla; Aginta, Windy; Safriandi, Ferry (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2024)
This test looks at the relationship between non-actual workplaces, hard work attitudes and work discipline on the efficiency of instructors and staff at Al-Azhar 1 Medan Private Elementary School. The population in this audit are educators and representatives at Al-Azhar 1 Medan Private Elementary School, with a target of 40 remaining workers at Al-Azhar 1 Medan Private Elementary School being 40 people. The research results show that non-actual workplace (X1), hard work attitude (X2), work discipline (X3) have a fundamental influence on the efficiency of educators and representatives at Al-Azhar 1 Medan Private Elementary School. Meanwhile, non-actual workplace (X1), hard work attitude (X2) and work discipline (X3) influence the efficiency of teaching staff and representatives at Al-Azhar 1 Medan Private Elementary School (Y).